PENGARUH PENDAPATAN PREMI, HASIL INVESTASI DAN KLAIM TERHADAP CADANGAN DANA TABARRU’ (Studi Pada Perusahaan Asuransi Syariah Indonesia) - Faidana Riki Dwi Setiawan; Jeni Susyanti; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine : 1) Effect of Premium Income on Tabarru’ Fund Reserves: 2) Effect of Invesment Results on Tabarru’ Fund Reserves; 3) Effect of Claims on Tabarru’ Fund Reserves; 4) Effect of Premium Income, Invesment Results, and Claims on Tabarru’ Fund Reserves.This type of research is causal comparative, namely research with the characteristics of a causal relationship of two or more variables. Comparative causal research is an ex post facto type of research on data collected after the occurence of a fact or event. The population of the research  is that all sharia insurance companies both life insurance and sharia general insurance which are registered in the  Indonesia Sharia Insurance Association in 2013-2017, amounting to 63 companies. The sampling technique uses purposive sampling, which a criteria. Based on criteria, a sampel of 10 companies was obtained. The data used is secondary data obtained from the company’s official website. Data Analysis used descrptive statistical analysis, normality test, classic assumption test, hypothesis test and multiple linear regression test.This study resulted in: 1) Premium Income not effecting the tabarru’ fund reserves; 2) Invesment Results have a positive and significant effect on tabarru’ fund reserves; 3)claims not effecting the tabarru’ fund reserves; 4) Premium Income, Invesment Results and claims have a significant positive effect on Tabarru’ Fund ReservesKeyword : Premium Income, Investment results, Claim and Tabarru’ Fund reserves.